2016
DOI: 10.15761/cogrm.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Malposition and displacement of intrauterine devices–diagnosis, management and prevention

Abstract: Introduction: Malposition and displacement of IUDs is an important drawback of all conventional intrauterine devices which rely sole on size for uterine retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…12 Reduction of the incidence of IUCD displacement can be done by proper insertion technique, proper selection of cases and modifications of the IUCD (small sized IUCDs and frameless IUDs). 13 Embedment as diagnosed on USG, refers to IUCD penetration into the endometrium or myometrium without extension through the serosa. It may occur up to some degree in up to 18% of females with an IUCD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Reduction of the incidence of IUCD displacement can be done by proper insertion technique, proper selection of cases and modifications of the IUCD (small sized IUCDs and frameless IUDs). 13 Embedment as diagnosed on USG, refers to IUCD penetration into the endometrium or myometrium without extension through the serosa. It may occur up to some degree in up to 18% of females with an IUCD.…”
Section: Resultsmentioning
confidence: 99%
“…of cases with missing strings. 13,18 An expulsion rate 2-10 % in 1st year of use, has been quoted. 19 In our study spontaneous expulsion of IUCD in women with missed IUCD threads was found to be less (4.35%, n=3), as our study population included the interval insertions also.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature specifically pertaining to IUD displacement into a CS scar is limited. However, an IUD displacement is generally shown to have the potential to cause abnormal uterine bleeding and pain along with a rare perforation risk of 0.1-0.2%, a percentage that is higher with inexperienced clinicians, IUD placements prior to six months postpartum, nulliparity, and higher miscarriage rates [6,7]. Although provider experience may influence proper IUD placement, IUD displacement has been associated primarily with the discrepancy between the IUD and uterine width cavity [6].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, compared to patients with misplaced coppercontaining IUDs, patients with misplaced LNG-IUDs have lower risks of adhesion formation and contraceptive failure [8]. In the asymptomatic patient, current recommendations point to expectant management; in the symptomatic patient, removal followed by replacement is favorable [6].…”
Section: Discussionmentioning
confidence: 99%